Gastroretentive Drug Delivery Systems: Innovative Strategies for Enhanced Gastric Retention and Improved Oral Drug Absorption - Chasta, Pankaj; Chandrul, Kaushal Kishore (Journal of Neonatal Surgery, 2025)
Oral drug delivery is the preferred route of administration due to its convenience and patient compliance. However, it encounters limitations such as poor solubility, intestinal instability, and incomplete absorption resulting from rapid gastrointestinal transit. Gastroretentive drug delivery systems (GRDDS) have emerged as a strategy to address these challenges by prolonging gastric residence time and enhancing the bioavailability of drugs absorbed in the stomach or upper intestine. This review examines physiological factors influencing gastric retention, including gastric emptying, pH variations, and absorption windows. Various GRDDS approaches—such as floating, swelling/expandable, mucoadhesive, high-density, magnetic, and raft-forming systems—are analyzed with respect to their mechanisms, formulation strategies, and evaluation parameters. Both natural and synthetic polymers play a crucial role in designing these systems, while innovations like 3D printing, smart polymers, and nanotechnology expand their potential. Despite advancements, challenges persist in translating laboratory success to clinical outcomes. GRDDS represent an innovation for improving oral bioavailability, enabling site-specific targeting, and enhancing therapeutic efficacy for drugs with narrow absorption windows or localized gastric action